The effects of exchange rate volatility on ASEAN-China bilateral exports - Yusoff, Mohammed; Sabit , Ahmed Hossain (IACSIT Press, 2015)
The paper examines the impact of exchange rate volatility, real GDP of China, and real exchange rates on the bilateral exports of ASEAN member countries to China using the generalized method of moments. The results show that all the coefficients of these variables have the expected signs and are statistically significant. Specifically, if exchange rate volatility goes up by 1 percent, the exports fall by about 0.21 percent; if real exchange rate depreciates by 1 percent, exports will increase by 1.12 percent, and when China’s real GDP increases by 1 percent, the ASEAN exports to China increase by 1.86 percent. The findings suggest that the ASEAN member nations should maintain the stability of their bilateral exchange rates with Chinese Yuan as a means to boost their exports to China.